Diminished Resistance to Hyperoxia in Brains of Reproductively Senescent Female CBA/H Mice - Šarić, Ana (Med Sci Monit Basic Res, 2015)
BACKGROUND: We have explored sex differences in ability to maintain redox balance during acute oxidative stress in brains of mice. We aimed to determine if there were differences in oxidative/antioxidative status upon hyperoxia in brains of reproductively senescent CBA/H mice in order to elucidate some of the possible mechanisms of lifespan regulation. MATERIAL/METHODS: The brains of 12-month-old male and female CBA/H mice (n=9 per sex and treatment) subjected to 18-h hyperoxia were evaluated for lipid peroxidation (LPO), antioxidative enzyme expression and activity - superoxide dismutase 1 and 2 (Sod-1, Sod-2), catalase (Cat), glutathione peroxidase 1 (Gpx-1), heme-oxygenase 1 (Ho-1), nad NF-E2-related factor 2 (Nrf2), and for 2-deoxy-2-[(18)F] fluoro-D-glucose ((18)FDG) uptake. RESULTS: No increase in LPO was observed after hyperoxia, regardless of sex. Expression of Nrf-2 showed significant downregulation in hyperoxia-treated males (p=0.001), and upregulation in hyperoxia-treated females (p=0.023). Also, in females hyperoxia upregulated Sod-1 (p=0.046), and Ho-1 (p=0.014) genes. SOD1 protein was upregulated in both sexes after hyperoxia (p=0.009 for males and p=0.011 for females). SOD2 protein was upregulated only in females (p=0.008) while CAT (p=0.026) and HO-1 (p=0.042) proteins were increased after hyperoxia only in males. Uptake of (18)FDG was decreased after hyperoxia in the back brain of females. CONCLUSIONS: We found that females at their reproductive senescence are more susceptible to hyperoxia, compared to males. We propose this model of hyperoxia as a useful tool to assess sex differences in adaptive response to acute stress conditions, which may be partially responsible for observed sex differences in longevity of CBA/H mice.